Employee Satisfaction: Determinants And Its Effect On Performance - Nurhidayati; Nunik Kusnilawati; Aprih Santoso (Jurnal Manajemen, 2022)
This study aims to examine the effect of competence, motivation, education on satisfaction and the effect of competence, motivation, education on performance and satisfaction on performance. The research method uses quantitative methods and the sample consists of 96 people consisting of employees who graduated from the University of Semarang who graduated a maximum of 3 years. The analytical tool used is SEM - PLS. The result of the analysis is that competence has no effect on satisfaction, but does affect performance. Motivation and education affect satisfaction and performance, and satisfaction affects performance.